Increases in the risk of cognitive impairment and alterations of cerebral β-amyloid metabolism in mouse model of heart failure. - Xiaoqi Hong; Liping Bu; Yi Wang; Jing Xu; Jian Wu; Yufang Huang; Jie Liu; Haiyun Suo; Lumeng Yang; Yuncen Shi; Yi Lou; Zhengliang Sun; et al. (PLoS ONE, 2013)
Epidemiological and clinico-pathological studies indicate a causal relationship between heart disease and Alzheimer's disease (AD). To learn whether heart disease causes an onset of AD, mice with myocardial infarction (MI) and congestive heart failure (HF) were used to test neuropsychiatric and cognitive behaviors as well as for measurements of AD related protein markers. To this end, adult mice were subjected to ligation of left anterior descending artery (LAD) and about two weeks later high-frequency echocardiography was performed to exam the resulting cardiac structure and function. Three months after successful induction of chronic heart failure (CHF) these mice showed an impairment of learning in the Morris Water Maze task. In addition, the expression of selected molecules, which are involved in β-amyloid metabolism, apoptosis and inflammation on the level of gene transcription and translation, was altered in CHF mice. Our findings provide a plausible explanation that CHF increases the risk of cognitive impairments and alters cerebral β-amyloid metabolism. In addition, our data indicate that the cerebral compensatory mechanisms in response to CHF are brain area and gender specific.